IMMUNOMODULATORY EFFECTS OF LISOVIT® IN RESPONSE TO NEWCASTLE DISEASE AND INFECTIOUS BURSAL DISEASE VACCINES IN BROILERS - A. Qayyum; A. Yousaf; T. Ahmad; Z. U. Rehman; U. Farooq (Journal of Animal and Plant Sciences, 2012)
The present study was designed to investigate effects of Lisovit® (Biomin, Austria) on the immune system of broiler chickens. For this purpose, 270 (day-old) broiler chicks were randomly divided into three groups A, B and C of 90 birds each. The birds were vaccinated against Newcastle Disease (ND) on day 3 (intraocular) and day 18 (drinking water) of age and against Infectious Bursal Disease (IBD) on day 8 (intraocular) and day 21 (drinking water) of age. Group A served as control, while birds of groups B and C were offered Lisovit® (Biomin, Austria) at the dose rate of 100 and 200 mg/kg body weight (b.wt.) respectively on days 22, 24 and 26 of age. The serum samples were collected at day 21, 31 and 41 of age and subjected to haemagglutination inhibition (HI) and indirect haemagglutination (IHA) antibody titres for ND and IBD vaccines, respectively. On day 13 post vaccination against ND, maximum values of the geometric mean haemagglutination inhibition (GMHI) antibody titres of groups A, B and C were 33.51,185 and 244, respectively. Whereas on day 10 post vaccination against IBD, maximum values of geometric mean indirect haemagglutination (GMIHA) antibody titres of groups A, B and C were 35.09, 255.19 and 387.01, respectively. The group C achieved significantly (p<0.05) higher antibody titres than group B and A. Feed conversion ratio (FCR) of group C was found better than group B and A. Mortality rate upto 42 days of age was significantly (p<0.05) lower in group C (2.2%), followed by B (13.3%) and highest in A  (29.0%). These results indicate that Lisovit® at the dose rate of 200mg/kg b.wt. can be used to enhance antibody titres against ND and IBD vaccines, to reduce mortality rate and to improve FCR in broiler chickens.
Keywords: Lisovit; antibody titre; FCR; mortality rate; broilers.